Integration of value stream mapping with DMAIC for concurrent Lean-Kaizen: A case study on an air-conditioner assembly line - Wei Guo; Pingyu Jiang; Lei Xu; Guangzhou Peng (Advances in Mechanical Engineering, 2019)
This article proposes a new model for concurrent Lean-Kaizen based on the Lean production thinking. According to the concept and application scenarios of value stream mapping and DMAIC (Define, Measure, Analyze, Improve, and Control), we proposed an integrated VSM-DMAIC by adopting their advantages and avoiding their disadvantages. The VSM-DMAIC model is applied to tackle the production problems on production line. Value stream mapping is used to identify the production problems during production processes by waste identification. Then, the production problems are clustered into different production problem sets according to the changed types of production resources while solving production problems. The data envelopment analysis method is used to rank the production problems by input–output ratio, and the most important production problem in each set can be the concurrent Lean-Kaizen. DMAIC provides a structured problem-solving method for production problems. Finally, the production problems and production problem sets will be reassessed for the next concurrent Lean-Kaizen. A case study of an air-conditioner assembly line verified the feasibility and efficiency of the proposed VSM-DMAIC model, which can be used to improve the economic benefits and decrease the waste of production line.